Optimizing Resource Allocation in Hierarchically Distributed Data Centers - Vieira, Rafael F.; Teixeira, Carlos A. M.; Cardoso, Diego L. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2019)
The current networks infrastructure needs to support the rapidly increasing data traffic. Sophisticated planning approaches must be adopted by the operators so the high number of applications can be managed efficiently. In this work, a resource provisioning model for hierarchically distributed data centers is proposed using Integer Linear Programming (ILP). The objective is to increase the efficiency in the use of computational resources and decrease the overhead in network links. Results show that, the model is able to efficiently accommodate 20% more applications when compared to the First-Fit approach.